Growth regulation of bermudagrass (Cynodon dactylon) and zoysiagrass (Zoysia japonica) with glyphosate - Dias, Roque C. [UNESP]; Tropaldi, Leandro [UNESP]; Dadazio, Tais S. [UNESP]; Macedo, Gabrielle C. [UNESP]; Silva, Paulo V.; Carbonari, Caio A. [UNESP]; Velini, Edivaldo D. [UNESP] (Taylor & Francis, 2021)
Glyphosate can generate positive effects on turfgrass maintenance as a form of growth control by decreasing the expenses associated with mowing. However, there is little information about the effects of this herbicide on turfgrasses. This study aimed to evaluate the response of bermudagrass and zoysiagrass to the herbicide glyphosate as a growth regulator. Two studies were performed in a greenhouse and repeated at different times. The treatments involved application of glyphosate at 10 different rates (0, 5.625, 11.25, 22.5, 45, 90, 180, 360, 720, and 1.440 g ae ha−1) with four replicates. Evaluations of green cover by digital analysis, injury, and plant height were performed at 7, 14, 21, and 28 days after application, and shoot dry matter of clippings was determined for the last evaluation period. Bermudagrass and zoysiagrass presented variedtolerance to glyphosate toxicity. Overall, the digital analysis showed that green content was negatively influenced by the increase in visual injury caused by glyphosate application. Moreover, increasing the glyphosate rate decreased plant height and shoot dry matter in both turfgrasses. Glyphosate application rates up to 45 g ae ha−1 for bermudagrass and 90 g ae ha−1 for zoysiagrass decreased plant growth without affecting the factors analyzed in this study.
Keywords: EPSPS; herbicide; low rates; plant growth regulator; turfgrass